Fraktographische Bruchspannungs‐Analyse von Acrylglas. Issue 1 (25th March 2019) - Brokmann, Christopher; Berlinger, Marcel; Schrader, Peer; Kolling, Stefan
Abstract : Fractographic fracture stress analysis of acrylic glass . Fractographic analyses of the fracture surfaces in brittle materials allow an evaluation of the fracture stress on basis of fracture mirrors which appear in the origin of failure. In the present work, this methodology is applied to non‐ideal brittle materials like PMMA (acrylic glass or Plexiglas ® ). A procedure is presented for determining the material‐dependent fracture mirror constant. For this purpose, the fracture mirror radii are measured and evaluated on more than 50 tensile specimens. Hereby, the non‐linear stress‐strain behaviour of PMMA and the fracture stresses are determined experimentally by digital image correlation. In order to validate the fracture mirror analysis on PMMA, the resulting statistical fracture stress distribution is compared to the distribution from digital image correlation. The presented method allows to determine the fracture stress even for complex component geometries after failure.